ANALISA SISTEM PENGENDALIAN INTERNAL PEMASANGAN RUMPON DALAM MENINGKATKAN PENDAPATAN MASYARAKAT NELAYAN DI KECAMATAN BANTAN DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Susi Susi; Risman Hambali (Bertuah: Journal of Sharia and Islamic Economics, 2020)
This research is done by the researcher’s concern about the income of the fishing community due  the lack of an internal installing rumpon control system  for fisherman in Bantan Sub Disrict by the Bengkalis Ministery of Maritime Affairs and Fisheries. By applaying the Rumpon intallation control system can increase fisherman income. Islam has taught the concept of leadership that  able carry out the controlling role. It is related to the income of the society. There are two formulations, 1) how is an internal rumpon installation control system can increase fishermans’ income in Bantan sub district. 2) Is an internal rumpon instalation control system in increasing has accordance with Islamic economic. This is a field research with qualitiative approach. There are 25 samples. The research finding shows the internal rumpon instalation control system that have done by the ministery of maritime affairs and fisheries is not effective. The data have showed that the income of the fisherman is not increase after the instalation, less of socialization about the system to the fishermans. The application of the internal rumpon instalation control system is not accordance of Islamic economic. Actually,  the installation of internal rumpon control system aim is to increase fishermans’ income and the welfare of the fishing community. Keywords: Interal Control, Rumpon, Income.